Negotiating the family order and the initiation of methamphetamine use in Japan - Brewster, David (Criminology & criminal justice, 2022)
This article uses the concept of the “negotiated order” as developed by McAra and McVie to focus on the role and nature of the “family order” in shaping the initiation of methamphetamine use in Japan. Presenting empirical qualitative data from multiple life-story interviews with 11 men with a history of methamphetamine use, the findings demonstrate that while there were variegated paths that led to initiation of use, a common factor was family breakdown and exclusion. Given the “group-oriented” nature of social organization and relations in Japan and the risks emanating from marginalization from “insider” groups, understanding the importance of the ways in which the ascription and negotiation of identities within and around the family can lead to initiation in a severely stigmatized and criminalized activity in this cultural context provides useful lessons for thinking about formal and informal responses to illegal drugs.